2010
DOI: 10.2337/db09-1431
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Inhibits Neuronal Apoptosis and Elevated Ca2+/Calmodulin-Dependent Protein Kinase II Activity in Diabetic Mouse Retina

Abstract: OBJECTIVEThis study investigated the effects of resveratrol, a natural polyphenol with neuroprotective properties, on retinal neuronal cell death mediated by diabetes-induced activation of Ca2+/calmodulin-dependent protein kinase II (CaMKII).RESEARCH DESIGN AND METHODSDiabetes was induced in C57BL/6 mice by five consecutive intraperitoneal injections of 55 mg/kg streptozotocin (STZ). Control mice received buffer. All mice were killed 2 months after the injections, and the extent of neuronal cell death, CaMKII,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 45 publications
0
47
1
5
Order By: Relevance
“…Increased cellular apoptosis is reportedly associated with Bax overexpression and the latter may be responsible for neuronal cell loss in the GCL of diabetic rats [26] . Additionally, Ca 2+ /calmodulin-dependent protein kinase II is possibly involved in the cell death pathway of RGCs in the STZ-induced diabetic retina [27] . Furthermore, protein kinase C-δ activation apparently contributes to neuroretinal apoptosis in the diabetic rat by inhibiting Akt-mediated signaling pathways [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Increased cellular apoptosis is reportedly associated with Bax overexpression and the latter may be responsible for neuronal cell loss in the GCL of diabetic rats [26] . Additionally, Ca 2+ /calmodulin-dependent protein kinase II is possibly involved in the cell death pathway of RGCs in the STZ-induced diabetic retina [27] . Furthermore, protein kinase C-δ activation apparently contributes to neuroretinal apoptosis in the diabetic rat by inhibiting Akt-mediated signaling pathways [27] .…”
Section: Discussionmentioning
confidence: 99%
“…111,112 Changes in intracellular calcium signaling as a result of extracellular glutamate activity or changes in the expression of calcium-binding proteins and the activity of calcium-responsive enzymes such as CamKII could also alter the physiological output of the retina. 62,113 Early compromise of specific visual functions, such as contrast sensitivity and dark adaptation, are indicators of functional changes within the photoreceptors or other neuronal components of the retina. 114 -117 Alterations in the biochemistry and physiology of retinal neurons may occur independently or as a precursor to their ultimate demise by apoptosis, making loss of visual function a potential consequence of cell loss by apoptosis and maladaptive dysfunction of surviving cells.…”
Section: The Potential For Loss Of Neuronal Function In the Absence Omentioning
confidence: 99%
“…9,48,49 Previous studies, which have investigated the relationship between diabetes and CaMKII, have reported that diabetes stimulates the action of CaMKII, which plays an important role in the pathogenesis of diabetic complications, such as diabetic retinopathy. [49][50][51][52] In this study, we found that compared with the healthy rats of the control group, active CaMKII (p-CaMKII) and cleaved caspase-3 levels were significantly increased in STZ-induced diabetic rats. However, these increases in the levels of active CaMKII (pCaMKII) and cleaved caspase-3 levels were minimized by treating the diabetic rats with curcumin.…”
Section: Curcumin Inhibits Retinal Neuronal Lossmentioning
confidence: 68%
“…Our results agree well with the results of a study that showed resveratrol, another polyphenol whose physiological properties are similar to those of curcumin, suppresses CaMKII action and CaMKII-mediated RGC loss induced by diabetes. 50 We have not been able to clearly determine the precise mechanism by which curcumin inactivates CaMKII action and prevents neuronal death. However, we believe that this mechanism is also involved in the regulation of glutamate levels.…”
Section: Curcumin Inhibits Retinal Neuronal Lossmentioning
confidence: 99%